Lymphoma of the uterine cervix – a rare clinical presentation - Petrović Rodić, Dušica; Kastratović, Tatjana; Jovanović, Danijela; Marković, Vladan; Stojanović, Jasmina; Jovanović, Dalibor (Vojnosanitetski pregled, 2023)
Introduction. Lymphomas are malignant diseases of the lymphocyte lineage. There are two basic types of lymphoma: Hodgkin's lymphoma (HL), whose main characteristic is the presence of Reed-Sternberg cells, and non-Hodgkin's lymphoma (NHL), which presents a heterogeneous group of diseases, and depending on the growth rate and the course of the disease, they can be indolent (slow-growing) and aggressive (fast-growing). Follicular lymphoma (FL) is the most common indolent form of NHL, while diffuse large B-cell lymphoma (DLBCL) is the most common aggressive form. Case report. The study presents a case of NHL, DLBCL, localized in the cervix, histopathologically diagnosed in a 35-year-old woman who, after a cervical biopsy, was histopathologically diagnosed with mild dysplasia (CIN1/L-SIL) of the cervical epithelium and, after that, an infection with human papillomavirus (HPV) subtypes 16 and 31 was proven. The diagnosis of DLBCL was histopathologically confirmed on a conical section of the vaginal portion of the uterus, after which the disease was treated with eight cycles of chemotherapy according to the RCHOP protocol. Conclusion. The coexistence of CIN1/L-SIL and NHL is random. However, this fact may cause the concomitant cervical lymphoma to be overlooked since the lymphoma is usually subepithelial if biopsies are not taken adequately and if HPV serotyping of the biopsy sample is not performed.
Keywords: biopsy; lymphoma, non-hodgkin; papillomaviridae; serotyping; uterine cervical dysplasia